Performance evaluation of liner dual barrier system in CO2-rich geothermal wells. (September 2021) - Ahmed, Shawgi; Patel, Harshkumar; Salehi, Saeed; Ahmed, Ramadan; Teodoriu, Catalin
Highlights: Challenges of production liner in geothermal wells Liner dual barrier system failure mechanisms Performance evaluation of dual barrier under corrosive downhole conditions. Finite element modeling of liner cement and seal assembly Identify liner cement safe downhole pressure operating boundaries Abstract: Geothermal well construction typically consists of a slotted production liner to support the wellbore and provide a conduit for produced reservoir fluids. To maintain the integrity of the well, the production liner is designed with a dual barrier system - a seal assembly at the top of the liner and a cement sheath between the formation and the liner. The integrity of barrier elements can compromise due to the degradation caused by acidic gases such as H2 S and CO2 that usually exist in geothermal reservoirs. In this paper, experimental and numerical studies were conducted to evaluate dual barrier system's performance and identify its failure modes at various downhole conditions. In this study, an experimental setup was designed to replicate the production liner dual barrier system consisting of a cement sheath and elastomer O-rings. The hydraulic and mechanical integrity of the seal assembly and the cement sheath barriers were investigated by conducting pressure tests. EPDM elastomer and neat class H cement were used as the barrier materials. The performance of elastomer was investigated after aging in an autoclave at 1000 psi and 180°F under CO2 exposure. The performance of the cement was evaluated at different wait on cement (WOC) intervals. Verified finite element models (FEM) were developed to simulate the response of barrier elements under different conditions. Results indicated that exposure to CO2 compromised the hydraulic integrity of the seal element. The structural integrity of the elastomer was also jeopardized after CO2 aging, as evident by the blisters and cracks visually detected on elastomers' surfaces. Verification by sealability test indicates that FEA modeling can be a reliable tool for estimating seal performance if elastomer material properties are known for the design conditions. Simulation results demonstrate that CO2 exposure can reduce the sealability of EPDM elastomer (measured in terms of contact stress) by up to 37%. For cement, the experimental results demonstrated insufficient interfacial bonding between cement and the inner pipe, as evidenced by the leak pathways observed during the hydraulic integrity tests. WOC time improves the hydraulic integrity of cement barrier element. Mechanical properties of cement cured at the elevated temperatures of up to 350°F were used in the FEA model to investigate the impact of temperature and wellbore pressure load on cement integrity. The results revealed that tensile hoop stress induced by the wellbore pressure loads is a likely failure mechanism that compromises the mechanical integrity of cement in geothermal wells. Results indicate that neat Class H cement may not serve as a reliable barrier in case of a defective seal assembly of a liner hanger. Overall, this paper identifies some of the barrier elements' major limitations and provides recommendations for designing barriers and improving well integrity.